The War Against Terror and Transatlantic Information Sharing: Spillovers of Privacy or Spillovers of Security? - Tzanou, Maria (Utrecht Journal of International and European Law, 2015)
The EU-US Passenger Name Record (PNR) agreement has been among the most controversial instruments in the fight against terrorism that the EU negotiated with the US after the 9/11 terrorist attacks. The agreement has been heavily criticised for its implications regarding fundamental rights, in particular the rights to privacy and data protection. Nevertheless, the EU has put forward plans to develop its own PNR programme. The present article aims to examine the new dynamics concerning privacy that arise from the transatlantic fight against terrorism. It argues that, while attempts for the development of a transatlantic privacy protection framework have been made, ‘spillovers’ of security, taking the form of internalisation of external counter-terrorism measures, are prevalent in the era of the war against terror.